Common Fixed Point Theorems for Multivalued β∗-ψ-Contractive: Tanusri Senapati, Lakshmi Kanta Dey - Team, Support (Thai Journal of Mathematics, 2017)
The aim of this article is to present some common fixed point theorems for multivalued β∗−ψ-contractive mappings. We also prove the existence and uniqueness of common fixed point for multivalued α∗-admissible mappings with respect to the function η∗. Our results extend several results in the literature. Suitable examples are presented to substantiate our main results.